Penerapan Metode Bermain dan Media Pendukung untuk Meningkatkan Kemampuan Gerak Dasar Lompat dan Loncat pada Siswa Kelas III SD Negeri Airlangga 1/198 Surabaya - Muhammad Naufal Marwan; Dony Andrijanto; Luthfi Aidin (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study aims to improve the basic motor skills of jumping and hopping among third-grade students at SD Negeri Airlangga 1/198 Surabaya through the implementation of play-based methods and supporting media. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this research are 30 third-grade students with varying abilities in basic locomotor skills, particularly in jumping and hopping. The results of the study indicate that the application of play-based methods and supporting media significantly improves students' basic motor skills in jumping and hopping. In the first cycle, there was a 20% improvement from the students' initial abilities, while in the second cycle, the improvement reached 35%. Moreover, the students were more enthusiastic and actively engaged in the learning activities. This demonstrates that an interactive play-based approach and the use of supporting media can enhance students' basic motor skills and create a more enjoyable and effective learning environment. Thus, this study recommends the implementation of play-based methods and supporting media as an effective teaching strategy to enhance basic motor skills in elementary school students, particularly in jumping and hopping lessons.